A escrita como processo de construção do conhecimento: uma análise das produções textuais dos alunos do 6° ano do colégio São Francisco Xavier - SOUSA, José Maria Ferreira de (2024)
This present work has who theme the write that process of construction of the learning. An analyze of the textual produces of the students in 6th year of the San Francisco high school, located on the Abaetetuba city. The work had who objective the uses of write who gear of the acquisition of the ability for if produce texts. So, how abstract our perception scientific, choose for execute methodology the research of field in qualitative approach. The place choose for the realize of the research was the San Francisco Xavier high school. Having make read and write of theorist that care about the objective of studies and behind analyze the data collection in field, terminate that the practice of the language write is reference construction and consistence on process of appropriation of the gears linguistics relation the textual producers. On the true how more the student if habilitate the write, more will have the opportunity of the become involved textually with that write, well how acquire subsidizes conceptual amount to habit if read and write.